SUBALTERN MOVEMENTS: PERSPECTIVE OF THE PRIMAL PEOPLE: . - Vadakumchery , Johnson (Journal of Dharma, 1998)
A group of university students from a city went to reside in a remote tribal village, Their plan was to spend there a few days. It was already evening when they reached the destination. The surroundings of the village were really enchanting and enthralling, that they decided to take stroll around the village and satisfy their curiosity.